International Investor Obligations: Towards Individual International Responsibility for the Public Interest in International Investment Law - Abel, Patrick (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
International investment law has been criticised for years: Do investors enjoy international rights without corresponding responsibility? This book challenges this view. On the contrary, treaty and arbitration practice is already subject to dynamics introducing international investor obligations, systematised by this book as direct and indirect obligations. Inter alia, these relate to the protection of human rights and the environment. This development may potentially reorient the field towards the principle of sustainable development and may even turn it into an international instrument to regulate investors’ behaviour. The book situates these findings in the broader context of general international law.